Modulation of Leishmania (L.) amazonensis Growth in Cultured Mouse Macrophages by Prostaglandins and Platelet Activating Factor - M. V. C. Lonardoni; C. L. Barbieri; M. Russo; S. Jancar (Mediators of Inflammation)
The role of endogenously synthesized PAF and prostaglandins on the infection of mouse macrophages by Letsbmanta (L.) amazonensis was investigated, as well as the possible correlation between the effects of these inflammatory mediators with nitric oxide production. It was found that pretreatment of macrophages with 10−5 M of the PAF antagonists, BN-52021 or WEB-2086, increased macrophage infection by 17 and 59%, respectively. The cyclooxygenase inhibitor, indomethacin (10 μg/ml), induced a significant inhibition which was reversed by addition of PGE (10-3 M) to the culture medium. These results suggested that the infection of macrophages by leisbmanla is inhibited by PAF and enhanced by prostaglandins and that these mediators are produced by macrophages during this infection. This was confirmed by addition of these mediators to the culture medium before infection; PAF (10−6, 10−9 and 10−12M) reduced significantly the infection whereas PGE2 (10−5 M) induced a marked enhancement. This effect of exogenous PAF on macrophage infection was reversed by the two PAF antagonists used in this study as well as by the inhibitor of nitric oxide synthesis, L-arginine methyl ester (100 mM). Taken together the data suggest that endogenous production of PAF and PGE2 exert opposing effects on Lesbmana–macrophage interaction and that nitric oxide may be involved in the augmented destruction of parasites induced by PAF.